2016
DOI: 10.1080/14686996.2016.1152879
|View full text |Cite
|
Sign up to set email alerts
|

The chemical, mechanical, and physical properties of 3D printed materials composed of TiO 2 -ABS nanocomposites

Abstract: To expand the chemical capabilities of 3D printed structures generated from commercial thermoplastic printers, we have produced and printed polymer filaments that contain inorganic nanoparticles. TiO2 was dispersed into acrylonitrile butadiene styrene (ABS) and extruded into filaments with 1.75 mm diameters. We produced filaments with TiO2 compositions of 1, 5, and 10% (kg/kg) and printed structures using a commercial 3D printer. Our experiments suggest that ABS undergoes minor degradation in the presence of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 35 publications
3
72
0
1
Order By: Relevance
“…Based on FDM especially the processing of composite filaments poses a great challenge as they consist of the thermoplastic polymer as printable binder matrix and typically inorganic or hybrid solid particles as filler material. For example, Sorkski et al used FDM to print an active catalyst for the photo degradation of Rhodamine 6G by incorporating TiO 2 nanoparticles into ABS filament . Another recent example by Sun et al is the catalysis of the Fenton oxidation of aromatic molecules by a catalytic monolith made from a PLA filament containing an iron catalyst .…”
Section: Introductionmentioning
confidence: 99%
“…Based on FDM especially the processing of composite filaments poses a great challenge as they consist of the thermoplastic polymer as printable binder matrix and typically inorganic or hybrid solid particles as filler material. For example, Sorkski et al used FDM to print an active catalyst for the photo degradation of Rhodamine 6G by incorporating TiO 2 nanoparticles into ABS filament . Another recent example by Sun et al is the catalysis of the Fenton oxidation of aromatic molecules by a catalytic monolith made from a PLA filament containing an iron catalyst .…”
Section: Introductionmentioning
confidence: 99%
“…This observation is in contrast with our observations for TiO 2 composites in which we found that the TiO 2 , and not the thermal processing, affected the glass transition temperature of the composite. 27 The result indicates that any interaction between the polymer and the MOF does not significantly affect the polymer-polymer interaction.…”
Section: Resultsmentioning
confidence: 95%
“…This conclusion is corroborated by our previous study with printed ABS-TiO 2 composites where molecules in aqueous solution could access nanoparticles within a printed structure. 27 For applications that involve chemical storage, this property is crucial because it shows that storage can be optimized by increasing the content of MOF content of the composite.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, researchers are presently experimenting with 3-D printed ABS containing inorganic TiO 2 nanoparticles to enhance various mechanical and chemical properties. 3 …”
Section: Introductionmentioning
confidence: 99%